2023
DOI: 10.29228/jrp.400
|View full text |Cite
|
Sign up to set email alerts
|

HPLC-DAD Screening and Antioxidant Activity of Phenolic Compounds of Salvia balansae de Noé Leaves Extract

Mohamed Malik MAHDJOUB,
Nourelimane BENZITOUNE,
Yacine MAIZ
et al.

Abstract: Salvia balansae de Noé is known to be an important source of a wide variety of non-toxic bioactive compounds with lack of information hinders exploitation in food and pharmaceutical industries as natural antioxidants. In this work, the phenolic compounds from S. balansae leaves were extracted using an ultrasound-assisted methodology and were separated and identified by HPLC-DAD. The antioxidant activity was evaluated by ABTS, and DPPH scavenging assays, Iron (Fe 2+ ) Chelating ability and reducing power (FRAP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
0
3
1
Order By: Relevance
“…Our findings exhibited a higher scavenging ability than those of Mahdjoub [27], who evaluated the hydroethanolic extract of S. balansae leaves and reported lower IC 50 values of 328.95 ± 5.29 and 545.03 ± 3.267 µg/mL for the ABTS and DPPH assays, respectively. Furthermore, Mekki [26] noticed that the antioxidant values of the aqueous extract of S. balansae leaves, as measured by the DPPH, ABTS, and total antioxidant capacity (TAC) assays, had values higher than the standard used, which is Trolox.…”
Section: Antioxidant Propertiescontrasting
confidence: 69%
See 3 more Smart Citations
“…Our findings exhibited a higher scavenging ability than those of Mahdjoub [27], who evaluated the hydroethanolic extract of S. balansae leaves and reported lower IC 50 values of 328.95 ± 5.29 and 545.03 ± 3.267 µg/mL for the ABTS and DPPH assays, respectively. Furthermore, Mekki [26] noticed that the antioxidant values of the aqueous extract of S. balansae leaves, as measured by the DPPH, ABTS, and total antioxidant capacity (TAC) assays, had values higher than the standard used, which is Trolox.…”
Section: Antioxidant Propertiescontrasting
confidence: 69%
“…Other compounds, such as 6,7-dihydroxycoumarin caffeic acid, p-coumaric acid, coumarin, trans-2-hydroxycinnamic acid, and trans-cinnamic acid, were detected in trace amounts (Table 3 and Figure 1). To the best of our knowledge, only the study of Mahdjoub [27] investigated the qualitative-quantitative analysis of phenolic compounds of an extract of S. balansae leaves. The HPLC-DAD analysis showed that there were 12 detectable phenolic compounds, and the total identified compound amounts ranged from 0.26 to 71.11 mg/g DW, representing two major classes: phenolic acids and flavonoids.…”
Section: Quantitative Analysis Of Phenolic Compounds By Hplc-dadmentioning
confidence: 99%
See 2 more Smart Citations